1992
DOI: 10.1111/j.1365-2109.1992.tb00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluoxymesterone on sex ratio and growth of Nile tilapia, Oreochromis niloticus (L.)

Abstract: The androgenic and anabolic potential of fluoxymesterone (FM) was evaluated by incorporating the hormone into the feed of Nile tilapia, Oreochromis niloticus (L.) fry. Phenotypic all-male populations were produced when FM was given at 1, 5 and 25mg/kg of feed. Fry fed methyltestosterone (MT) at 60 mg/kg of feed and 0-2 mg of FM per kg of feed had a sex ratio of 97-7% and 87-3% phenotypic males.No positive anabolic effect was evident in response to adding FM or MT to the feed at the end of the 28-day treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
4
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
6
4
1
Order By: Relevance
“…In this study, we observed a relatively high male percentage (90:18%) compared to the females in those groups fed with androgenised feed compared to those not subjected to the hormone. These results in terms of male to female percentage are similar to other findings [17][18][19] implying that 17-α methyl testosterone hormone is an effective androgen in sex reversal even in open environments. However, our findings male; female sex ratios (90 ± 1.10: 18 ± 1.54 %) were rather low compared to the other researchers [17,20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, we observed a relatively high male percentage (90:18%) compared to the females in those groups fed with androgenised feed compared to those not subjected to the hormone. These results in terms of male to female percentage are similar to other findings [17][18][19] implying that 17-α methyl testosterone hormone is an effective androgen in sex reversal even in open environments. However, our findings male; female sex ratios (90 ± 1.10: 18 ± 1.54 %) were rather low compared to the other researchers [17,20].…”
Section: Discussionsupporting
confidence: 90%
“…These results in terms of male to female percentage are similar to other findings [17][18][19] implying that 17-α methyl testosterone hormone is an effective androgen in sex reversal even in open environments. However, our findings male; female sex ratios (90 ± 1.10: 18 ± 1.54 %) were rather low compared to the other researchers [17,20]. Even though the feeding rate was similar, fed at 20% body weight four times a day, a low male percentage observed in our study seem to be highly correlated to the low temperature (19-24°C) compared to 26°C used by Phelps et al [17].…”
Section: Discussionsupporting
confidence: 90%
“…However, the percentage of males obtained from the 40 (93.4%) and 60 mgMT/kg (94.4%) fish was insignificant (P>0.05).The proportion of males is consistent to what was reported by Phelps et al [33] (97.8% males), and [7] (96.8% males) on O. niloticus who set their experiment in hapas for 28 days at 60 mgMT/kg feed the protocol similar to the current study. Shepperd [34] and Celik et al [11] found similar results on Red tilapia in steel tank and aquaria on O. niloticus respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Similar results were also observed for protein efficiency ratio. Matty and Lone (1979) and Matty (1980 &1981) demonstrated that natural androgens and MT treatment enhanced the feed efficiency values in common carp, Cyprinus carpio L. Also, Phelps et al, (1992) obtained similar results when O. niloticus fry was fed the diet treated with MT at 60 mg/kg of feed for 28 days.…”
Section: Feed Conversion Ratio (Fcr)mentioning
confidence: 85%